Case study of midwifery care for postpartum mothers on day 4 with breast milk dams - Hendriyadi, Dhea Wahyu Chendra Ningrum (LPPM Universitas dr. Soebandi, 2024)
Abstrak After giving birth is a critical period in breastfeeding because breastfeeding problems in mothers arise. Such as irregular breast milk and breast milk stagnation, breast milk production is said to be smooth if there is excessive breast milk production which is indicated by breast milk dripping and gushing out heavily when sucked by the baby. According to data from the registration book in the KIA room in January-February at the Kamal Health Center, there were 25% of postpartum mothers with irregular breast milk including breast milk stagnation from 16 postpartum mothers. The occurrence of breast milk stagnation is caused by irregular breast milk production, because the baby does not breastfeed often enough from its mother. This disorder can be worse if the mother rarely breastfeeds her baby, as a result the baby does not get breast milk exclusively and if not treated immediately it will cause breast milk stagnation. This incident results in a dilemma for the mother, namely the accumulation of breast milk in the breast, as a result of which it can cause swelling. As for the psychological impact on the mother, the mother feels anxious and feels unable to breastfeed her baby. This case study aims to determine the description of midwifery care for postpartum mothers on the 4th day with breast milk stagnation. The method used in this case study is one case study. Using a case study approach to midwifery care involving primary and secondary data collection, anamnesis and physical examination techniques, comprehensive analysis and management with periodic evaluation. The target of midwifery care in this case study is P1A0 day 4 with breast milk dams carried out from April-May 2024 at the Kamal Health Center. After the data collection is compiled, the data obtained from the results of patient interviews and physical examinations can be presented in the form of midwifery documentation, namely SOAP. Based on the results of the data review, on the first visit it was found that the respondent complained of feeling breast pain and swelling, while the baby did not want to breastfeed the respondent because the nipples were flat causing breast milk not to come out if not pumped. On the second visit the respondent said she felt anxious because her breasts were still sore and swollen so that it was difficult to breastfeed her baby. There was also a second visit where the mother's temperature increased to 38 ℃. On the third visit, subjective data was obtained from the mother saying that her breasts were no longer painful when pressed and were not swollen and objective data from the mother's temperature had returned to normal. On the fourth visit, the mother said that she had no difficulty breastfeeding her baby and continued to pump breast milk when not breastfeeding her baby. From the results of subjective and objective data, the Analysis on the first and second visits was determined P1A0 with breast milk dams with problems of breast pain and anxiety. And on the third and fourth visits there was an analysis of P1A0 with breast milk dams that had been resolved. The midwifery care provided includes providing guidance on breast care, teaching mothers to express breast milk by pumping when not breastfeeding their babies, teaching mothers the correct techniques for breastfeeding and burping babies, providing education on how to increase breast milk production including nutritious food, adequate rest and peace of mind and soul, and reminding mothers to continue breast care at home. Complaints obtained from subjective and objective data are common complaints that occur in postpartum mothers who experience problems in breastfeeding, namely breast milk engorgement. Breast swelling is caused by breastfeeding that is not done continuously which causes the remaining breast milk to collect in the duct area, resulting in narrowing of the lactiferous ducts, resulting in breast milk engorgement. Midwifery care carried out on respondents from the beginning of the complaint to the end has been carried out well according to theory. The conclusion of the case study of midwifery care for postpartum mothers with breast milk engorgement was successfully carried out well because the mother's condition improved and complications were successfully anticipated. It is hoped that health workers can improve ANC services, especially in preparation for breastfeeding by examining the condition of the mother's breasts and guiding mothers on how to care for their breasts, so that during the postpartum period the mother already knows about lactation preparation. and respondents are able to increase their knowledge and apply what has been directed by health workers about breast care and preparation for breastfeeding.